Hubungan Status Fisik American Society of Anesthesiologist (ASA) dengan Pencapaian Waktu Pulih Bromage Score pada Pasien Post Anestesi Spinal di RSUD dr. R. Goeteng Taroenadibrata Purbalingga - Salsabila, Kamilia Tasya; Yudono, Danang Tri; Suandika, Made (IAI Nasional Laa Roiba Bogor, 2025)
Spinal anesthesia is a method of anesthesia by injecting local anesthetic drugs into the subarachnoid space in the lumbar region. The Bromage Score is used to assess the recovery of motor function in the lower extremities and to determine the patient's readiness to be transferred from the recovery room to the inpatient ward. The recovery level of motor function is influenced by various factors, including the patient's physical status assessed through the American Society of Anesthesiologists (ASA) classification. This study aims to determine the relationship between ASA physical status and the time to achieve the Bromage Score in post-spinal anesthesia patients at RSUD dr. R. Goeteng Taroenadibrata Purbalingga. This study used a survey research design with a cross-sectional approach, where each subject was observed once, and measurements were conducted simultaneously. The study results showed that the patient age distribution was 22 people (38.5%), gender distribution was 39 people (68.4%), Body Mass Index (BMI) was 31 people (54.4%), and drug type usage was 57 people (100%). Patients with ASA II physical status numbered 35 people (61.4%), and the time to achieve a Bromage Score < 4 hours was found in 32 people (56.1%). The conclusion is that there is a significant relationship between the physical status of the American Society of Anesthesiologists (ASA) and the time to achieve the Bromage Score in post-spinal anesthesia patients at RSUD dr. R. Goeteng Taroenadibrata Purbalingga, with a p-value of 0.001 (p < 0.05).